2008
DOI: 10.1159/000111511
|View full text |Cite
|
Sign up to set email alerts
|

What Characterizes the Severity of Psoriasis?

Abstract: Background: Understanding the epidemiology of moderate-to-severe psoriasis is essential for its management. Objective:To assess the epidemiological characteristics of patients with moderate-to-severe psoriasis. Methods: Cross-sectional, observational epidemiological study conducted in Spain and Portugal. Data were collected by 332 dermatologists for ≧10 consecutive presenting patients. Results: Based on body surface area (BSA) and Psoriasis Area and Severity Index (PASI) criteria, moderate-to-severe psoriasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 101 publications
1
9
0
1
Order By: Relevance
“…One systematic review of the literature found that psoriatic arthritis can affect 24% of psoriasis patients. 25 The AQUILES study findings are very similar to those reported by García-Díez et al 26 after a cross-sectional study that evaluated the characteristics of patients with moderate or severe psoriasis in Spain and Portugal. The authors found that 13% of these patients had psoriatic arthritis.…”
Section: Discussionsupporting
confidence: 84%
“…One systematic review of the literature found that psoriatic arthritis can affect 24% of psoriasis patients. 25 The AQUILES study findings are very similar to those reported by García-Díez et al 26 after a cross-sectional study that evaluated the characteristics of patients with moderate or severe psoriasis in Spain and Portugal. The authors found that 13% of these patients had psoriatic arthritis.…”
Section: Discussionsupporting
confidence: 84%
“…Another limitation of our study is that it was conducted in a tertiary care center (academic medical center), thus patients were biased toward having more severe Ps and possibly more comorbidities than the general Ps population. However, our practice is both a primary care and referral center for psoriatic patients; Ps disease activity in our patient population is generally similar to that of the Spanish Ps population (Caucasian) [54]. Another limitation of our study is the lack of data on the degree of eating habits and sedentary lifestyle of our patients, clearly related to low HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 96%
“…This proportion is higher than European surveys, in which moderate-to-severe psoriasis was confirmed by dermatologists in 79.3% of patients [39], and 74% of participating subjects considered their psoriasis as at least moderately severe [32]. In the absence of rigorous data enabling the characterization of psoriasis severity (apart from the PASI), classification of severe psoriasis was mostly recoded by study working group members, which may have led to bias.…”
Section: Discussionmentioning
confidence: 99%